(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
The article analyzed aspects of two recorded versions of the marchinha Yes, nós temos bananas, composed by Braguinha and Alberto Ribeiro. The song was released in January 1938, at the Carnival Revue of the same name, in Rio de Janeiro - and was a decisive part of its structure. Shortly afterwards, Almirante would record it for Odeon. The song was taken up again in 1967, in the play O rei da vela, staged by Teatro Oficina, and in May 1968 it was recorded by Caetano Veloso, by Phillips, with arrangement by Rogério Duprat. The combined analysis of these versions, their theatrical environment and their probable historical dialogues allowed to observe certain continuities in the ways in which culture dealt with the cycles of modernization in Brazil in the 20th century.